The Role of the General Election Supervisory Agency (BAWASLU) of Gayo Lues Regency in Resolving Disputes in the 2024 Election Process in Gayo Lues Regency, Aceh Province - Sri Yani S; Adam Adam; Heri Kusmanto (Universitas KH. Abdul Chalim Mojokerto, 2026)
The Gayo Lues Regency Election Supervisory Agency (Bawaslu) has a huge responsibility in overseeing and resolving election process disputes and is at the forefront of maintaining the integrity of elections at the local level. In resolving disputes in the 2024 election process, Bawaslu Gayo Lues Regency implemented a resolution mechanism through mediation and adjudication as stipulated in the legislation. This study aims to determine and analyze the role of the Gayo Lues Regency Election Supervisory Body (Bawaslu) in resolving disputes in the 2024 election process in Gayo Lues Regency, Aceh Province, and to identify factors that hinder the implementation of this role. The research method used was descriptive with a qualitative approach. Data collection techniques were carried out through observation, interviews, documentation, and literature study. Data analysis was conducted using the role theory of Horoeputri, Arimbi, and Sentosa, which includes roles as policy, roles as strategy, roles as communication tools, roles as dispute resolution, and roles as therapy. The results of the study indicate that the role of Bawaslu Gayo Lues Regency in resolving election process disputes The year 2024 has been implemented in accordance with the provisions of laws and regulations, but has not yet run optimally because it still faces several obstacles, including limited human resources, limited budget, inadequate facilities and infrastructure, limited time in resolving disputes, and low public understanding of the election process and election process disputes.